2011
DOI: 10.1007/s00425-011-1411-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of aconitase in citrus fruit callus results in a metabolic shift towards amino acid biosynthesis

Abstract: Citrate, a major determinant of citrus fruit quality, accumulates early in fruit development and declines towards maturation. The isomerization of citrate to isocitrate, catalyzed by aconitase is a key step in acid metabolism. Inhibition of mitochondrial aconitase activity early in fruit development contributes to acid accumulation, whereas increased cytosolic activity of aconitase causes citrate decline. It was previously hypothesized that the block in mitochondrial aconitase activity, inducing acid accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 59 publications
(85 reference statements)
5
33
0
Order By: Relevance
“…Aconitase activity of whole cell extracts and mitochondria-enriched fractions from control fibroblasts was progressively inhibited using increasing concentrations of citramalate (maximum inhibition at 80–100 mM, see online supplementary figure S2A). ACO1 activity remained unchanged even at high concentration of citramalate, demonstrating that citramalate selectively inhibits ACO2 in human cultured skin fibroblasts, as shown in plants 6. The use of citramalate allowed to directly measure the ACO2 and ACO1 activities in whole cell extracts from control and patients’ fibroblasts.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Aconitase activity of whole cell extracts and mitochondria-enriched fractions from control fibroblasts was progressively inhibited using increasing concentrations of citramalate (maximum inhibition at 80–100 mM, see online supplementary figure S2A). ACO1 activity remained unchanged even at high concentration of citramalate, demonstrating that citramalate selectively inhibits ACO2 in human cultured skin fibroblasts, as shown in plants 6. The use of citramalate allowed to directly measure the ACO2 and ACO1 activities in whole cell extracts from control and patients’ fibroblasts.…”
Section: Resultsmentioning
confidence: 73%
“…Aconitase activity (ie, consumption of cis -aconitate) was coupled to that of native isocitrate dehydrogenase, at 340 nm, in the presence of 0.8 mM Nicotinamide adenine dinucleotide (NAD), 0.8 mM Nicotinamide adenine dinucleotide phosphate (NADP) and 0.10 mM MgCl 2 . The reaction was initiated by adding 5 mM cis -aconitate to the medium, either in absence or in the presence of 100 mM potassium citramalate monohydrate (Sigma Aldrich), a potent inhibitor of ACO2 in citrus fruit 6. Protein amounts were quantified using Bradford reagent (BioRad).…”
Section: Methodsmentioning
confidence: 99%
“…This fact coupled with the central point of this enzyme in the regulation of organic acid metabolism, aconitase seems to be a potential and suitable target for metabolic engineering applications. For instance, the recent combination of genetic and molecular approaches has demonstrated the crucial role of this enzyme in controlling organic acid content in ripe tomato fruit (Morgan et al 2013), whereas in citrus fruit it was possible to manipulate the fruit acidity by changes in amino acid metabolism (Degu et al 2011). …”
Section: Resultsmentioning
confidence: 99%
“…At the later stage of fruit development and maturity, the γ‐aminobutyric acid (GABA) shunt could effectively reduce cytosolic acidity by catabolizing the glutamate produced as a product of citrate metabolism (Cercós et al ). When the aconitase inhibitor (citramalic acid) was used to treat citrus callus, it was found that excessive citric acid was transformed into amino acids via the GABA shunt (Degu et al ). The above‐mentioned studies showed that the GABA shunt is involved in the regulation of organic acid metabolism.…”
Section: Introductionmentioning
confidence: 99%